Nyctalus noctula - Voon-Ching Lim; Rosli Ramli; Bhassu, Subha; John-James Wilson (Zenodo, 2017)
Nyctalus noctula [Schreber, 1774] (?) Vespertilios noctula Schreber, 1774: 166, pl. 52; FRANCE (Collector unknown; Type unknown) [202]. Nyctalus noctula [8]. Common English name: Eurasian Noctule Barcode Index Number: DNA barcodes recorded as N . noctula are associated with BIN, BOLD: AAC 7411, but there are no DNA barcodes from Peninsular Malaysia. Remarks: Chasen [8] suggested that the species in Peninsular Malaysia may represents N . n . labiate = labiatus Hodgson, 1835 (type locality = Nepal) which also occurs in Pakistan and India [9]. N . n . labiatus is considered to be morphologically distinct from N . noctula and therefore, should be raised as a species [203]. The records of N . noctula from Peninsular Malaysia, if valid, may be referable to “labiatus” or “plancyi” [203]. IUCN status: Least Concern Recorded at: There is only one record of N . noctula in this region which is an old skin dated 1838 purchased in Singapore [204] but its origin remains doubtful [23]. Based on the purchased skin, Dobson [204] included Peninsular Malaysia in the distribution range of N . noctula , which was followed by Corbet and Hill [9] and Medway [23]. We could not find recent records for the species although it is thought to occur in Peninsular Malaysia [1, 10]. We found two old records which reported two specimens of Nyctalus sp. in a National Park, Pahang [87] and Ulu Langat Forest Reserve, Selangor [88]. However, there are no specimens deposited in the DWNP collection. N . noctula roosts in tree hollows and forages high above canopy [14, 23]. : Published as part of Voon-Ching Lim, Rosli Ramli, Subha Bhassu & John-James Wilson, 2017, A checklist of the bats of Peninsular Malaysia and progress towards a DNA barcode reference library, pp. 1-65 in PLoS ONE 12 (7) on page 47, DOI: 10.1371/journal.pone.0179555, http://zenodo.org/record/4251352 : {"references": ["202. Schreber JC. Die Saugethiere. Abbildungen nach der Natur mit Beschreibungen, vol 1. Erlangen: Wolfgang Walther. 1775.", "8. Chasen FN. A handlist of Malaysian mammals (A systematic list of the mammals of the Malay Peninsula, Sumatra, Borneo and Java, including the adjacent small islands). Bulletin of the Raffles Museum; 1940.", "9. Corbet GB, Hill JE. The mammals of the Indomalayan region: a systematic review. Oxford: Oxford University Press; 1992.", "203. Csorba G, Hutson AM. Nyctalus noctula; 2016 [cited 2017 Jan 16]. Database: The IUCN Red List of Threatened Species 2016: e. T 14920 A 22015682 [Internet]. Available from: http: // dx. doi. org / 10.2305 / IUCN. UK. 2016 - 2. RLTS. T 14920 A 22015682. en.", "204. Dobson GE. Catalogue of Chiroptera in the collection of the British Museum. London: Bristish Museum; 1878.", "23. Medway L. The wild mammals of Malaya. London: Oxford University Press. 1969.", "1. Davison GW, Zubaid A. The status of mammalian biodiversity in Malaysia. Status of Biological Diversity in Malaysia and Threat Assessment of Plant Species in Malaysia. Kuala Lumpur: Forest Research Institute Malaysia; 2007. pp. 3 - 27.", "10. DWNP. Red list of mammals for Peninsular Malaysia. Department of Wildlife and National Parks Peninsular Malaysia; 2010.", "87. Yatim SH, Baatu Z, Saaidun KA, Marzuki MI. Survey of mammals and bird species in six different habitats: mangrove, lowland dipterocarp, hill dipterocarp, upper dipterocarp, montane oak and montane ericaceous forest. Journal of Wildlife and Parks. 1985; 4: 65 - 91.", "88. Yatim SH. A preliminary survey on inventory habitat and wildlife in the Ulu Langat Forest Reserve and Sungai Dusun Game Reserve. Journal of Wildlife and Parks. 1983; 2: 119 - 140.", "14. Francis CM. A field guide to the mammals of South-East Asia. New Holland Publishers; 2008."]}